Identifying Effective Factors on Technological Entrepreneurship in Iranian Nanotechnology SMEs - Pakrad, Mahdi; ., Reza Mohammad Kazemi (Information Management and Business Review, 2012)
Technological entrepreneurship is the latest issue in the field of entrepreneurship and fostering competitive advantages in Small and Medium Enterprises (SMEs) which has been received special attention. Given the lack of coherent literature review to apply technological strategies in SMEs, and also because of the role of technology based firms which are active in industries with new technologies, such as Nano-Technology industry, while the technological entrepreneurship literature review has been investigated, this article is principally intended to identify effective factors on technological entrepreneurship in Iranian Nanotechnology SMEs. The research methodology of the current article is a mixed one; in the qualitative stage, semi-structured and open interviews and investigation of related documents have been used, and in the quantitative stage, the questionnaire has been applied to gather data. In the researchâ€™s quantitative stage, a statistical population consisted of managers, expert employees of the case study have been considered, and the simple random sampling method has been used. In addition, in this stage, the questionnaires have been used as the data collection tool and the experts in the qualitative stage measured the researchâ€™s validity, and the questionnaireâ€™s reliability has been approved through Cronbachâ€™s alpha of 0.81. The mean analysis has been applied in this stage for the data analysis. The findings of this paper shows that the effective factors on technological entrepreneurship in Iranian Nanotechnology SMEs are categorizes in the four issues of â€œInternal Processesâ€, â€œIndividual Factorsâ€, â€œInstitutionsâ€ and â€œExternal Networksâ€.